Geoprocessamento e sensoriamento remoto aplicado na determinação da aptidão agrícola de uma microbacia - Corseuil, Cláudia Webber [UNESP]; Campos, Sérgio [UNESP]; Ribeiro, Fernanda Leite; Pissarra, Teresa Cristina Tarlé [UNESP]; Rodrigues, Flavia Mazzer [UNESP] (My University, 2009)
Soil use for the development of activities as agriculture and livestock has been causing great alterations in the environment, mainly when these are practiced intensively, disrespecting the fragility and aptitude of the natural resources. Therefore, it is essential that the planning of the agricultural activities is done, taking into consideration the several environmental criteria involved in the decision-making process. Thus, this study aimed to analyze the agricultural aptitude classes of lands from a watershed through geographical information system (GIS). The Arroio Ajuricaba watershed is located in the Municipality of Marechal Cândido Rondon - PR among the coordinates UTM 787309m E and 793892m E; 7275026m N and 7281310m N, in the Spindle 21, presenting an area of 1681ha. Soil maps, in semi detail scale, was the digital cartographic base used. The results allowed to conclude that 42.41% of the basin presented a good aptitude for farming in handling level of high technology (handling level C), regular aptitude for B, and restricted aptitude for A [class 1(a)bC] and that 12% of the area had regular aptitude for farming in the three handling levels (class 1abc). The watershed lands (14.24%) presented regular aptitude for farming in handling level C, restricted aptitude for B, and inapt for A [class of aptitude 2(b)c]; 15.85% presented good aptitude for planted pasture (class 4P) and 12.21% were considered without aptitude for agricultural use (class 6). We can say that 71.94% of the lands has aptitude for farming, although they present different degrees of limitations that request different treatments for its conservation.
Geoprocessing and remote sensing applied to determination of a watershed agricultural aptitude
Keywords: Agricultural aptitude; Geoprocessing; Soil units; agricultural application; agricultural soil; cartography; decision making; digital mapping; GIS; image processing; remote sensing; watershed; Brazil; Marechal Candido Rondon; Parana; South America